ANTESEDEN DAN KONSEKUENSI DARI CUSTOMER ATTITUDE DALAM INDUSTRI SKINCARE DI INDONESIA - Azra Zinedine Rahman; Fatik Rahayu (Lembaga Pengembangan Kinerja Dosen, 2025)
The skincare industry in Indonesia is experiencing rapid growth, driven by social media and the preferences of Generation Z and Millennials. This study examines the influence of influencer credibility, influencer attractiveness, and online customer reviews on consumer attitudes, as well as their impact on brand awareness, brand loyalty, and repurchase intention. Using a quantitative approach, a survey was conducted with 209 respondents who follow beauty influencers and purchase recommended products. Structural Equation Modeling (SEM) analysis reveals that influencer credibility and online customer reviews significantly influence consumer attitudes, leading to increased brand awareness and brand loyalty. However, influencer attractiveness does not have a significant effect on consumer attitudes. Furthermore, brand awareness positively contributes to repurchase intention, while brand loyalty does not show a significant impact. These findings provide insights for companies to optimize influencer-based marketing strategies in the increasingly competitive beauty industry.